2020
DOI: 10.3389/fimmu.2020.588387
|View full text |Cite
|
Sign up to set email alerts
|

Thermoneutrality and Immunity: How Does Cold Stress Affect Disease?

Abstract: One of the major challenges the scientific community faces today is the lack of translational data generated from mouse trials for human health application. Housing temperature-dependent chronic cold stress in laboratory rodents is one of the key factors contributing to lack of translatability because it reveals major metabolic differences between humans and rodents. While humans tend to operate at temperatures within their thermoneutral zone, most laboratory rodents are housed at temperatures below this zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 86 publications
0
48
0
Order By: Relevance
“…Humans, while maintaining the same body temperature, are thermoneutral at a much lower environmental temperature (∼24°C). Thus, although the majority of animal facilities operate at “room temperature,” research mice experience persistent cold stress under these conditions ( 76 78 ). This alteration in thermoregulation influences the basal metabolic rate and is therefore expected to affect all aspects of experimental results in mice, including microbiota findings.…”
Section: Temperature and Experimental Workmentioning
confidence: 99%
“…Humans, while maintaining the same body temperature, are thermoneutral at a much lower environmental temperature (∼24°C). Thus, although the majority of animal facilities operate at “room temperature,” research mice experience persistent cold stress under these conditions ( 76 78 ). This alteration in thermoregulation influences the basal metabolic rate and is therefore expected to affect all aspects of experimental results in mice, including microbiota findings.…”
Section: Temperature and Experimental Workmentioning
confidence: 99%
“…Constant mouse body temperature monitoring has led to the discovery of thermoneutral points that changes according to the active or resting daily phases of mice (135). Last but not least, studies based on the use of a fixed 'humanset' thermoneutral housing condition have often reported contrasting effects on a wide range of disease conditions (113). As an example, from the perspective of an immune response to infection, thermoneutrality has been reported to both alleviate or exacerbate signs of disease (131,136,137).…”
Section: Discussionmentioning
confidence: 99%
“…Research on hyperphagia in the context of weight maintenance in mice suggests that this behaviour is likely to be secondary to increased energy expenditure to homeostatically control body temperature (109)(110)(111). This was rather interesting in light of a large body of recent work that links the immune response to metabolism and temperature control (112)(113)(114). Indeed, studies have shown that thermoneutral temperatures for mice (30-33°C) -as opposed to standard research laboratory temperatures of 22°C (a temperature that is tolerable for human caregivers) -simultaneously alter the host immune system and its metabolism (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…In menopausal women, HF are caused by core body temperature elevations acting within a greatly narrowed thermoneutral zone [51] The lowering of the upper threshold in menopause changes peripheral blood flow even with a slight rise in core body temperature, which results in HF. Basic scientific investigations [52] have determined that narrowing of the thermoneutral zone is caused by increased brain norepinephrine levels. Acupuncture can stabilize the thermoregulatory center by influencing serotonin and norepinephrine in the central nervous [41,53,54].…”
Section: Discussionmentioning
confidence: 99%